Does High Total Ischemic Time Have a Different Impact in Patients with st-elevation Myocardial Infarction Depending on Renal Function ? - Petrosyan, Harutyun; Hayrapetyan, Hamlet; Veprintseva, Anastasiia; Torozyan, Shahen; Ghazaryan, Norik (Cardiology and Cardiovascular Medicine, 2024)
Aim: The purpose of this study was to compare the influence of high total ischemic time (TIT) on in-hospital complications and prognosis in STsegment elevation myocardial infarction (STEMI) patients with different renal functions. Methods: A total of 224 STEMI patients with ≥ 6 hours TIT were selected for this study and divided into three groups according to GFR. Group 1 comprised 73 patients with < 60 ml/min/1.73 m2 GFR. Group 2 consisted of 72 patients with ≥ 60 ml/min/1.73 m2 and < 90 ml/min/1.73 m2 and Group 3 comprised 79 patients with ≥ 90 ml/min/1.73 m2. The groups' other characteristics were similar. The primary outcome was a 6-month death rate after admission for STEMI, and secondary outcomes were in-hospital death and complication of STEMI with lung edema (LE) or cardiogenic shock(CS). Results: The incidence of LE and CS was significantly lower in Group 3 (1.3%) compared to Group 1 (15.1%) and Group 2 (6.9%) (p = 0.006). LE and CS rates did not differ significantly between Group 2 and Group 3 (p =0.103). No significant between-group differences were found for inhospital death in Group 1 (4.1%), Group 2 (1.4%), and Group 3 (0) (p = 0.15). Also, the authors found significant between-group differences for 6-month death. Group 1 (12.3%) showed a considerably higher 6-month death rate than Group 2 (2.8 %) and Group 3 (2.5%) (p=0.015). No significant between-group differences were found for the 6-month death rate in Group 2 and Group 3 (p = 0.999). Conclusion: STEMI patients with RD, a high level of TIT had a great impact on nosocomial complications and prognosis compared to STEMI patients with normal kidney function. Key Points: Our study showed that in STEMI patients with RD, a high level of TIT had a great impact on nosocomial complications and prognosis compared to STEMI patients with normal kidney function. This was discovery of a clear relationship between RD and in-hospital complications and prognosis in the case of high TIT. Impaired renal function in patients with TIT, as an aggravating factor, doctors should pay due attention to avoid fatal complication. The result of the study gives us the opportunity to predict more likely complications in STEMI patient and be ready for them to choose the appropriate treatment.